PENGEMBANGAN E-LKPD BERBASIS LIVEWORKSHEET DENGAN PENDEKATAN KONTEKSTUAL TERHADAP PEMECAHAN MASALAH MATEMATIS PADA PESERTA DIDIK KELAS VII SMP/ MTs - Bemi, Adek Tiwi Wucika (Jurnal Edukasi dan Penelitian Matematika, 2023)
Abstract - The purpose of this study is to provide Electronic Learner Worksheets (E-LKPD) for students in junior high school's VIIth grade who need to solve mathematical problems in context. The Plomp model is used in the creation of this liveworksheet-based E-LKPD. The process of creating an E-LKPD using live worksheets includes a preliminary needs analysis, curriculum development, concepts, student evaluation, and self-evaluation. Questionnaires, interviews, and observations were the sources of data for this preliminary research. According to preliminary investigation, E-LKPD are required to help students develop their problem-solving abilities, and students are interested in using interactive, effective LKPDs that can be accessed on liveworksheet. The E-LKPDs were then created and assessed independently in relation to the mistakes made when utilizing them. Liveworksheet-based E-LKPDs and self-evaluations have been created based on the initial study and can be verified by specialists.Keyword: E-LKPD, Contextual Teaching and Learning, Mathematical Problem Solving Abilites, Liveworksheet